2010
DOI: 10.1007/s11575-010-0053-0
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Accommodation and Language Priming

Abstract: 0 this paper explores three arguments. First, cultural accommodation by living in another culture for a while may have a long-lasting but partially dormant influence on behavior. Second, foreign language is a prime, activating behavior associated with this language. third, a foreign language is expected to be a particularly forceful prime for those who have lived in a country where this language is spoken. We explore this logic in a prisoner's dilemma quasi-experiment that focuses on competitive versus coopera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…Binding foundations are related to the domain of human morality because they serve the social functions of limiting autonomy and self-expression for the good of social communities such as families, teams, and nations (Graham and Haidt, 2010). Cross-cultural research on moral codes has revealed that various societies rely on different interpersonal moral codes to regulate behavior: collectivistic cultures such as India and Japan emphasize social harmony and a duty-based interpersonal moral code, while individualistic cultures such as the United Kingdom and the United States stress autonomous voluntarism and an individually oriented moral code (Markus and Kitayama, 1991;Miller, 1994;Singelis et al, 1995;Akkermans et al, 2010).…”
Section: Moral Foundation Theorymentioning
confidence: 99%
“…Binding foundations are related to the domain of human morality because they serve the social functions of limiting autonomy and self-expression for the good of social communities such as families, teams, and nations (Graham and Haidt, 2010). Cross-cultural research on moral codes has revealed that various societies rely on different interpersonal moral codes to regulate behavior: collectivistic cultures such as India and Japan emphasize social harmony and a duty-based interpersonal moral code, while individualistic cultures such as the United Kingdom and the United States stress autonomous voluntarism and an individually oriented moral code (Markus and Kitayama, 1991;Miller, 1994;Singelis et al, 1995;Akkermans et al, 2010).…”
Section: Moral Foundation Theorymentioning
confidence: 99%
“…These contexts underline that US and Australia contrast against Singapore; consequently, if the results are consistent across the three countries, they signify that findings are robust across several contexts. Practically, the common use of the English language across the three countriesdespite the contrasts in individualist-collectivist orientation, valuation of social order, norms, and participation-mobilization-minimizes experimenter effects from language (Akkermans, Harzing, and Witteloostuijn 2010;Cameron et al 2009). …”
Section: T H E C O U N T R I E S F O R E X P E R I M E N T : a U S T mentioning
confidence: 99%
“…Our reliance on secondary data, which enables us to conduct a large-scale multi-year analysis spanning far-flung countries also drives our reliance on country-level data for the linguistic diversity and native languages of the partners' corporate teams. Although our study lacks precise controls for the effects of corporate language policies, employment practices, cultural accommodation, and language priming resulting from the use of English as lingua franca (Akkermans, Harzing, & Van Witteloostuijn, 2010), our empirical approach of clustering around both the MNC and design firm in the dyad, compensates for the lack of these variables that are not measured explicitly with our data. Within our focal interface, the exact composition of the corporate teams and the combination or sequence of cognitive tasks is not fully observed.…”
Section: Limitations and Future Directions For Further Researchmentioning
confidence: 99%
“…One highly promising area is experiments that manipulate various aspects of language use to trigger and carefully isolate the causal mechanisms linking language differences to differences in thinking (Akkermans et al, 2010;Boroditsky, 2010b;Keysar et al, 2012;. Another interesting avenue is to empirically compare and contrast the effect of language friction in business situations that require varying frequencies and levels of crossborder interaction.…”
Section: Limitations and Future Directions For Further Researchmentioning
confidence: 99%